Distorted niobium-self-doped graphene in-situ grown from 2D niobium carbide for catalyzing oxygen reduction. (November 2018) - Li, Wenqiang; Amiinu, Ibrahim Saana; Zhang, Bingwen; Zhang, Chengtian; Zhang, Zhiwei; Zhu, Jiawei; Liu, Jing; Pu, Zonghua; Kou, Zongkui; Mu, Shichun
Abstract: Developing high activity graphene-based materials for oxygen reduction reaction (ORR) catalysts remains a key issue for potential applications in fuel cells. According to the DFT calculation results, the distorted niobium-doped graphene (Nb-G) can process the high oxygen adsorption energy (ΔE) on Nb-G that improves the O2 coverage on surfaces of catalysts. Further we find nitrogen (N) can activate Nb-G with higher ΔE and lower work function than Nb-G, promoting the adsorption of O2 and breakage of O–O bond, in favor of the ORR performance. Before constructing N-activated Nb-G (N-Nb-G) materials with few-layer atomic layers, Nb-self-doped graphene is obtained from the 2D niobium carbide (NbC) only by one step incomplete chlorination reaction created by our group. This structural conversion from 2D NbC to Nb-G is accompanied by in-situ Nb doping which successfully overcomes the serious mismatch of lattices between carbon and transition metal atoms. The obtained N-Nb-G by annealing the mixture of melamine and Nb-G shows much enhanced ORR activity (The half-wave potential is 0.824 V). Undoubtedly, this work adds a family member of carbon-based materials with high ORR catalytic performance. Graphical abstract: Image 1